The soft landing problem for an infinite system of second order differential equations - Ibragimov, Gafurjan; Rakhmanov, Askar; Alias, Idham Arif; Jaffar, Mai Zurwatul Ahlam Mohd (American Institute of Mathematical Sciences, 2017)
We study a soft landing differential game problem for an infinite system of second order differential equations. Control functions of pursuer and evader are subject to integral constraints. The pursuer tries to obtain equations and at some time and the purpose of the evader is opposite. We obtain a condition under which soft landing problem is not solvable.